A new species of Eurypogon Motschulsky (Coleoptera: Artematopodidae) from China, with notes on E. sanzang Wang & Liu - Packova, Gabriela; Háva, Jiří; Wang, Cheng-Bin; Kundrata, Robin (Zootaxa, 2023)
Eurypogon Motschulsky, 1859 is a small artematopodid genus from the Nearctic and Palaearctic realms, with only three species known from mainland China. Here, we describe Eurypogon schuhi Packova & Kundrata, sp. nov. from the Hubei province in China, which is similar in the black body coloration to the recently described Eurypogon sanzang Wang & Liu, 2021 from the Henan province. Both species differ mainly in the ratio of basal antennomeres, elytral surface and proportions, and shape of male genitalia. We report populations of E. sanzang from the Qinling Shan in the Shaanxi province (a new province record) and from the Xiong’er Shan in the Henan province. Additionally, we describe the female of E. sanzang and discuss intraspecific variability in male genitalia. We provide images of main diagnostic characters for both species.